2022
DOI: 10.3390/catal12080926
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Reaction Mechanism of Molybdenum Metal in Direct Coal Liquefaction Residue

Abstract: In this paper, the extraction residue of direct coal liquefaction residue-DCLR(ER) was used as raw material. The high-temperature reaction mechanism of Mo compound in DCLR(ER) was investigated using a synchronous thermal analyzer and the Factsage database. The high temperature reaction of DCLR(ER)-MoO3 in an oxygen atmosphere consists of pyrolysis of organic components at 400–600 °C, molybdenum trioxide sublimation at 747–1200 °C, and a stable stage at 600–747 °C. The thermal reaction process of the DCLR(ER)-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…To verify our conjecture, the thermal analyses of the Fe2O3-MoO3 mixtures with different ratios were conducted as shown in Figure 2c,d. It can be seen that the final re- A previous study reported that Fe 2 O 3 can react with MoO 3 at 710 • C to form Fe 2 Mo 3 O 12 [30], suggesting that Fe 2 O 3 can stabilize the MoO 3 during high-temperature sintering. To verify our conjecture, the thermal analyses of the Fe 2 O 3 -MoO 3 mixtures with different ratios were conducted as shown in Figure 2c,d.…”
Section: Thermal Analysis Of Precursorsmentioning
confidence: 83%
See 1 more Smart Citation
“…To verify our conjecture, the thermal analyses of the Fe2O3-MoO3 mixtures with different ratios were conducted as shown in Figure 2c,d. It can be seen that the final re- A previous study reported that Fe 2 O 3 can react with MoO 3 at 710 • C to form Fe 2 Mo 3 O 12 [30], suggesting that Fe 2 O 3 can stabilize the MoO 3 during high-temperature sintering. To verify our conjecture, the thermal analyses of the Fe 2 O 3 -MoO 3 mixtures with different ratios were conducted as shown in Figure 2c,d.…”
Section: Thermal Analysis Of Precursorsmentioning
confidence: 83%
“…This indicates that it is of great importance to prevent the evaporation of MoO 3 during the synthesis of SFMO. A previous study reported that Fe2O3 can react with MoO3 at 710 °C to form Fe2Mo3O12 [30], suggesting that Fe2O3 can stabilize the MoO3 during high-temperature sintering. To verify our conjecture, the thermal analyses of the Fe2O3-MoO3 mixtures with different ratios were conducted as shown in Figure 2c,d.…”
Section: Thermal Analysis Of Precursorsmentioning
confidence: 97%
“…The oxidation process of MoS 2 can occur inside an electrical furnace in presence of atmospheric oxygen. Molybdenum trioxide, which is converted in two stages as the reaction product between MoS 2 and O 2 , is produced (MoS 2 → MoO 2 → MoO 3 ), according to the reactions (8) and (9): 67,68 MoS 2 + 3O 2 → MoO 2 + 2.5SO 2 MoO 2 + 0.5O 2 → MoO 3 …”
Section: Resultsmentioning
confidence: 99%